Anthropologists, Indigenous Scholars and the Research Endeavour : Seeking Bridges Towards Mutual Respect. - Hendry, Joy (Routledge studies in anthropology., 2012)
This collection offers the fruits of a stimulating workshop that sought to bridge the fraught relationship which sometimes continues between anthropologists and Indigenous/Native/Aboriginal scholars, despite areas of overlapping interest. Participants from around the world share their views and opinions on subjects ranging from ideas for reconciliation, the question of what might constitute a universal ""science, "" Indigenous heritage, postcolonial museology, the boundaries of the term ""Indigeneity, "" different senses as ways of knowing, and the very issue of writing as a method of dissemi.